Disentangling the factorial structure of the Greek Big Five Questionnaire for Children – Short Form. (1st April 2020) - Kokkinos, Constantinos M.; Markos, Angelos; Michaelides, Michalis P.; Voulgaridou, Ioanna
Highlights: The factorial structure of the G-BFQ-C-SF was examined. A bifactor model consisting of a strong GPF but also 5 specific factors that accounted for the unique item variance emerged. Multigroup analyses indicated that measurement parameters of the best-fitting model were mostly invariant across gender. The scale was found to exhibit longitudinal measurement invariance over a six-month time span. Abstract: The Greek Big Five Questionnaire for Children – Short Form measures the Five Factor Model in childhood and early adolescence. Although the Big Five has been theoretically conceptualized as containing orthogonal dimensions, prior work has revealed noteworthy intercorrelations among the five dimensions suggesting the possible existence of, one or more, general factors underlying the correlations. The so-called General Factor of Personality can be conceived of as the highest-order dimension of personality and related psychological domains, a counterpart of the well-known g-factor in intelligence. The aim of the present research was to further validate the G-BFQ-C-SF's factorial structure by examining alternative higher-order and bifactor models in a large sample of young pre-adolescents. The results supported a bifactor model consisting of a moderate general factor but also five specific factors that account for the unique variance among the items. Multigroup analyses indicated that measurement parameters of the best-fitting model were mostly invariant across gender. Moreover, the scale was found to exhibit longitudinal measurement invariance over a six-month time span. The results of the present study may lead to a better understanding of early adolescent personality and can serve as a basis for more extensive research on the nature of the GFP.